IMPACTS OF CORPORATE DONATIONS ON THE BRAZILIAN ELECTIONS - Santana, Izabella Mariano; Selari, Leandro da Silva; Camila Vitória; Gabriel Henrique Xavier; Aysla Mendes Marins 3, Giovana; Vilela Medeiros, Lucas; Vitória Santos Araújo, Maria; Ribeiro Machado, Natália; Mota Silva, Thuanny (CIPEEX, 2025)
The financing of electoral campaigns in Brazil has undergone significant changes in recent years, especially after the ban on corporate donations by Law No. 13,165/2015. Prior to this, the predominant model was private financing, based on large contributions from companies. This system created imbalances in the electoral process, encouraging corruption, increasing the influence of economic interests over political decisions, and widening inequality. This study aims to analyze the impacts of the transition from private to public financing in Brazilian electoral campaigns, assessing whether this change strengthens democracy, ensures greater transparency, and promotes equality among candidates. The research was conducted through a legislative review, analyzing Law No. 13,487/2017, which established the Special Campaign Financing Fund (FEFC), funded by resources from the National Treasury. The study considers two forms of public financing: the direct form, which includes the party fund and the FEFC; and the indirect form, which refers to state incentives such as free use of media and public assets for the dissemination of campaign proposals. Despite the reduction of corporate influence, public financing is subject to criticism regarding the use of public funds for campaigns, which some believe should be allocated to essential areas identified by society. Furthermore, there is still inequality in the distribution of funds among political parties, highlighting the need for greater transparency and oversight. The adoption of public financing represents a democratic advancement but requires ongoing improvement. It is essential to strengthen oversight mechanisms and ensure a fair allocation of resources, thereby promoting more balanced and transparent elections.